INTERACTION OF CURRENT CARRIERS WITH OPTICAL PIEZOELECTRIC GRATING VIBRATIONS GYROTROPIC ¬CRYSTALS - И. М. Коканбаев (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents scientific research on the interaction of current carriers with optical piezoelectric oscillations of gyrotropic crystal lattices